Green Legality Certificate on Agrarian Reform: Indonesian Experience - Jaelani, Abdul Kadir; Octavia Kusumaningtyas, Reza; Dian Luthviati, Resti; Al Fatih, Sholahuddin; Siboy, Ahmad (KnE Social Sciences, 2024)
As the most essential human need, territory is crucial for the survival of humanity. The increase in population and demand for land, as a result of urbanization, can no longer satisfy human requirements. The research method in this study is a normative legal research method. The approach method uses a statute approach, a comparative approach, and an analytical approach. The green certification serves as evidence for the legality of a building, fulfilling the criteria for a green building, as well as supports the green movement, which contributes to a positive public image. In the future, unregistered land could receive electronic certificates for the first time through land registration. As a guarantee of ownership of land rights, the legislation provides holders of electronic certificates with legal protection. The electronic information and transaction law (IET Law) accepts electronic land certificates as proof of electronic tenure. Keywords: green legality, land, certificate, Agrarian reform